Optimizing Innovative Learning Strategies and Organizational Environment for Employee Development in Manufacturing Companies in Central Java - Amiruddin Qadaar; Achmad Sholihin; Dwita Setiyani; Arna Purtina (Universitas Tidar, 2024)
The aim of this research is to examine the direct influence of optimizing innovative learning strategies on employee development and to test whether the organizational environment mediates optimizing innovative learning strategies on employee development in manufacturing companies in Central Java. The total population of manufacturing company employees in Central Java in 2022 is approximately 43,975,786. Using the Slovin's formula, a sample of 348 employees is obtained with a confidence level of 5%. Stratified random sampling techniques are applied to select employee samples, ensuring a good representation of various manufacturing companies in Central Java. To analyze the data and test research hypotheses, the Multiple Linear Regression method with the assistance of SPSS software will be utilized. The results of this research are that innovative learning strategies have a significant effect on employee development and the organizational environment has a significant effect on employee development.